Interculturality, a challenge? - Brandner, Rudolf; García López, Isabel (Estudios de Filosofía, 1996)
The revolutionary process of ontological homogenisation during the last two centuries leads to conclude that preserving interculturality seems impossible. Interculturality, and the problems to it attached, appears as a concept preciselly when interculturality as a basic reality of human life is disappearing. This article presents this concept in a diachronical way and shows that it is the referent of a historical situation and of a human conditionfrom which we are already excluded.